Chemoradiation therapy in pregnant patients treated for advanced-stage cervical carcinoma during the first trimester of pregnancy: report of two cases. Issue 1 (1st January 2007) - Benhaim, Y.; Haie-Meder, C.; Lhommé, C.; Pautier, P.; Duvillard, P.; Castaigne, D.; Morice, P.
Abstract : Two patients treated using chemoradiation therapy (CRT) (with fetus in utero ) for advanced-stage squamous cell cervical carcinoma diagnosed during the first trimester of pregnancy are reported. One patient with a stage IVA disease diagnosed at 12 weeks of gestation was treated by exclusive CRT with the fetus in utero . She recurred 20 months after the end of the treatment. The second patient had a stage IIB disease diagnosed at 12 weeks of gestation and was treated by CRT with the fetus in utero followed by completion surgery (radical hysterectomy and para-aortic lymphadenectomy) due to the presence of a suspicious residual disease. No residual disease was observed during the histologic analysis of hysterectomy and nodes specimens. This patient is alive and free of disease 24 months after surgery. Our observations could suggest that CRT in pregnant patients with fetus in utero is feasible without major short-term toxicity. Such management could be proposed in patients with a bulky cervical cancer diagnosed during the first trimester of the pregnancy. Management of the uterine evacuation depends on the local tumor spread.